2018
DOI: 10.1016/j.psychres.2018.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Internalised stigma in mental health: An investigation of the role of attachment style

Abstract: Internalised stigma is associated with a range of negative outcomes, yet little is known about what determines the internalisation of stigma. In this study we examined the potential role of adult attachment style in the internalisation process in a transdiagnostic sample of adults with experience of recent mental health service use (n = 122), using an online survey. Associations between internalised stigma and perceived public stigma were tested. We also examined whether anxious and avoidant (insecure) attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Permissible social distance in relation to mentally ill patients among psychiatrists was significantly more distant than among patients, which is consistent with previous studies [26,27], confirming the high level of stigmatization of patients by society and psychiatrists. The chance of having friendships and family relationships with this population was 5.4 times higher among the patients than doctors, indicating a lower level of stigma in patients.…”
Section: Discussionsupporting
confidence: 90%
“…Permissible social distance in relation to mentally ill patients among psychiatrists was significantly more distant than among patients, which is consistent with previous studies [26,27], confirming the high level of stigmatization of patients by society and psychiatrists. The chance of having friendships and family relationships with this population was 5.4 times higher among the patients than doctors, indicating a lower level of stigma in patients.…”
Section: Discussionsupporting
confidence: 90%
“…This is known as anticipated stigma, which Earnshaw (2012) defines as the belief that discrimination will be directed at the self from others in the future, due to the stigmatised condition or identity. Moreover, the stigma surrounding ED diagnosis may mean that people feel labelled by their disorder, leading to the internalisation of stigmatising experiences, stemming from negative attitudes held by others (Bradstreet, 2018). This is often referred to as internalised stigma.…”
Section: Stigma Of Eating Disorders and Recovery-related Outcomesmentioning
confidence: 99%
“…Some people may find their identity empowers them and that they can use their anger to improve their own circumstances and help others. Indeed, research has demonstrated that public stigma and self-stigma are correlated, but not necessarily strongly associated (Bradstreet, Dodd, & Jones, 2018; Chronister, Chou, & Liao, 2013). Structural, or institutional stigma, occurs when policies, rules or regulations within society intentionally marginalise the opportunities of those with mental disorders or produce unintended consequences that hinder their prospects, resources and wellbeing (Corrigan, Markowitz, & Watson, 2004; Hatzenbuehler, 2016; Rusch & Thornicroft, 2014).…”
Section: Introductionmentioning
confidence: 99%